2013
DOI: 10.1097/tp.0b013e318279153c
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation With Kidneys Retrieved From Deceased Donors With Acute Renal Failure

Abstract: In this cohort of patients, kidneys from deceased donors with ARF provided graft survival and renal function comparable with kidneys from donors without ARF 1 year after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 20 publications
9
82
0
3
Order By: Relevance
“…The presence of AKI in the donor had no effect on the 1-year patient and graft survival, on the rate of acute rejections and on creatinine clearance within the first year. This finding applied to renal transplant recipients from extended criteria donors (n = 137 without AKI, n = 116 with AKI) and to recipients from standard criteria donors (n = 896 without AKI, n = 369 with AKI) [13]. Since these data were obtained from the USA and Brazil with DBDs of a comparably low mean age, they may not be transferable to Europe and/or considerably higher donor ages.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The presence of AKI in the donor had no effect on the 1-year patient and graft survival, on the rate of acute rejections and on creatinine clearance within the first year. This finding applied to renal transplant recipients from extended criteria donors (n = 137 without AKI, n = 116 with AKI) and to recipients from standard criteria donors (n = 896 without AKI, n = 369 with AKI) [13]. Since these data were obtained from the USA and Brazil with DBDs of a comparably low mean age, they may not be transferable to Europe and/or considerably higher donor ages.…”
Section: Introductionmentioning
confidence: 92%
“…Unexpectedly, the well-known adverse effect of delayed graft function (DGF) on graft survival could not be seen in recipients of AKI kidneys, but was evident in recipients of standard donor kidneys [12,18]. Klein et al [13] reported their extensive center experience in a study of 1518 renal transplant recipients between 1998 and 2008, including 485 transplants from a DBD with AKI (defined by a donor serum creatinine concentration >1.5 mg/dL). The presence of AKI in the donor had no effect on the 1-year patient and graft survival, on the rate of acute rejections and on creatinine clearance within the first year.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Demographic characteristics know to be associated with real function at 12 months may also account for this observation. For example, the incidence of DGF among deceased donor kidney transplant recipients is relatively high, ranging from 45 to 53%, despite no differences being present among the groups [15]. In the r-ATG/EVR group, the mean final creatinine of deceased donors was higher compared to the other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors directly or indirectly related to AKI have been evaluated in transplantation, including preservation technique, cold-ischemia time, and donor terminal creatinine (10), although many authors argue against discarding kidneys based on high creatinine levels alone (2,(11)(12)(13). Little attention, however, has been given to assessing the degree of structural AKI in the donor apart from conventional "proxy" measures such as cold-ischemia time or creatinine.…”
Section: Introductionmentioning
confidence: 99%